Visual Similarity Detection for Intellectual Property using Deep Transfer Learning - Alnafjan, Abeer; Aldayel, Mashael (Politeknik Elektronika Negeri Surabaya (PENS), 2025)
Trademarks examination can benefit from deep transfer learning. Utilizing pretrained models to extract image features can significantly improve the trademarks registration process. This approach can facilitate and accelerate image detection. This study aims to enhance the trademark similarity examination process by detecting marks’ visual similarities using deep transfer learning. Deep transfer learning has the potential to develop the registration process of trademarks through the implementation of an automated image detection system, which can enhance detection accuracy. To the best of our knowledge, no automated approach has been used locally to determine the similarities between local trademarks. This study proposes an image similarity detection system to make the trademark examination process more efficient and assist examiners in their decision-making. The proposed system was validated using a dataset provided by the Saudi authority for intellectual property (SAIP). To extract the features, we employed a residual network-based convolutional neural network model (ResNet-50). Then principal component analysis (PCA) was used to reduce the number of extracted features. The proposed system reached a mean average precision (MAP) of 0.774, which indicates a promising result in distinguishing the similarity of trademarks. The findings of this research suggested that an image similarity detection system can support decision-making in trademark examination contexts. Trademark examiners, legal professionals, and intellectual property offices can use the results of this research to enhance their evaluation processes and improve the accuracy and efficiency of trademark registration.